Liquid Chromatographic Method for Determination of Nisoldipine from Pharmaceutical Samples - Amit Gupta; Ram S. Gaud; S. Ganga (E-Journal of Chemistry)
A simple and specific high performance thin layer chromatographic method was developed and validated for the determination of nisoldipine from tablet dosage form. The method was carried out at 320 nm after extraction of drug in methanol. The method uses aluminum plates pre-coated with silica gel 60F-254 as stationary phase and cyclohexane-ethyl acetate-toluene (3:3:4, v/v/v) as mobile phase. Linearity was established over a range of 400-2400 ng per zone. Both peak area ratio and peak height ratio showed acceptable correlation coefficient i.e. more than 0.99. However we used peak area for validation purpose. Intra-day and inter-day precision was determined and found to have less than 6.0 % RSD.